Macrophage-derived extracellular vesicles transfer mitochondria to adipocytes and promote adipocyte–myofibroblast transition in epidural fibrosis - Feng Hua; Jinpeng Sun; Mohan Shi; Rui Mei; Zeyuan Song; Jun Liu; Mingshun Zhang (npj Regenerative Medicine)
Abstract Epidural fibrosis post laminectomy is the leading cause of failed back surgery syndrome. Little is known about the role and mechanisms of adipose tissues in epidural fibrosis. Here, we found that obese patients were more likely to develop epidural fibrosis after spine surgery. Similarly, obesity led to more progressive epidural fibrosis in a mouse model of laminectomy. Adipocyte–myofibroblast transition (AMT) occurs in epidural scarring. Mechanistically, large extracellular vesicles (EVs) from M2-type macrophages transfer mitochondria into adipocytes and promote AMT by activating the TGF-β and PAI-1 pathways. Blocking the PAI-1 pathway significantly attenuated the transition of adipocytes into myofibroblasts. We conclude that large EVs from macrophages transfer mitochondria to promote AMT in epidural fibrosis.